Network reconfiguration of distribution systems using metaheuristics and reliability measures - Da Silva, Armando M. Leite; Nascimento, Luiz C.; Cassula, Agnelo M. [UNESP]; Sacramento, Cleber E.; Ávila, Afonso F. (Institute of Electrical and Electronics Engineers (IEEE), 2009)
In an evermore competitive environment, power distribution companies need to continuously monitor and improve the reliability indices of their systems. The network reconfiguration (NR) of a distribution system is a technique that well adapts to this new deregulated environment for it allows improvement of system reliability indices without the onus involved in procuring new equipment. This paper presents a reliability-based NR methodology that uses metaheuristic techniques to search for the optimal network configuration. Three metaheuristics, i.e. Tabu Search, Evolution Strategy, and Differential Evolution, are tested using a Brazilian distribution network and the results are discussed. © 2009 IEEE.
Keywords: Differential evolution; Distribution system reliability; Distribution systems; Evolution strategy; Network reconfiguration; Tabu search; Competitive environment; Deregulated environments; Differential Evolution; Distribution network; Evolution strategies; Meta heuristics; Meta-heuristic techniques; Network re-configuration; Optimal network configuration; Power distribution company; Reliability Index; Reliability measure; System reliability index; Distributed parameter networks; Evolutionary algorithms; Intelligent systems; Local area networks; Pumps; Reliability